Pengaruh Biaya Produksi dan Biaya Promosi Terhadap Laba Bersih pada UMKM Teh Tarik Armanda - Livia Saputri; Sihabudin; Robby Fauji (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of this research is to determine the partial and simultaneous influence of production cost variables and promotional costs on the net profit of Teh Tarik Armanda MSMEs. The sampling strategy for this research combines a quantitative approach with descriptive verification techniques using purposive sampling techniques. For the 24 month period between 2022 and 2023, data on production costs, promotional costs and net profit are used in this research. Multiple linear regression analysis was used to evaluate the data, accompanied by simultaneous and partial hypothesis testing. Based on the research results, Teh Tarik Armanda's net profit is significantly influenced by the production cost variable of 0.000<0.05, but not significantly by the promotion cost variable of 0.092>0.05. In addition, Teh Tarik Armanda was simultaneously significantly impacted by both production costs and promotion costs (0.000<0.005).